1996
DOI: 10.1046/j.1365-2125.1996.37117.x
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of pulmonary vascular tone

Abstract: 1 The ability to manipulate pharmacologically pulmonary vascular tone independent of effects on systemic blood vessels is a desirable objective. Elucidation of the biochemical mechanisms underlying hypoxia-induced pulmonary vasoconstriction ( HPV) may permit preferential targeting of the pulmonary circulation. 2 Here we review our studies of the role of locally synthesized candidate vasoactive factors in HPV. In addition, we present data demonstrating an attenuated pressor response to hypoxia in the pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The pulmonary vascular and cardiac response to hypoxia is reduced markedly in the Fischer 344 rat strain compared with the Wistar-Kyoto strain [53], and a similar strain-related difference has been reported between Fischer 344 and Sprague-Dawley rats [54]. The differential response breeds true, and cannot be explained by differences in pulmonary vascular architecture.…”
Section: Hypoxia-induced Pulmonary Hypertensionmentioning
confidence: 55%
“…The pulmonary vascular and cardiac response to hypoxia is reduced markedly in the Fischer 344 rat strain compared with the Wistar-Kyoto strain [53], and a similar strain-related difference has been reported between Fischer 344 and Sprague-Dawley rats [54]. The differential response breeds true, and cannot be explained by differences in pulmonary vascular architecture.…”
Section: Hypoxia-induced Pulmonary Hypertensionmentioning
confidence: 55%
“…Previous studies with isolated perfused lung preparations have shown that the pressor response to acute hypoxia in the F-344 rat pulmonary circulation is ϳ50% of that produced in the WKY rat (25) and markedly reduced compared with outbred Sprague-Dawley rats (8). The F-344 rat pulmonary vascular response to other pressor stimuli such as angiotensin II, however, is similar to that observed in the WKY rat (25), and others (8) have found that pulmonary artery rings from F-344 rats contract as well as those from Sprague-Dawley rats to phorbol 12-myristate 13acetate, a protein kinase C activator. Taken together with our histological findings, the attenuated response of the F-344 rat to hypoxic pulmonary vasoconstriction does not appear to be due to a relative paucity of pulmonary vascular smooth muscle.…”
Section: Resultsmentioning
confidence: 94%
“…Taken together with our histological findings, the attenuated response of the F-344 rat to hypoxic pulmonary vasoconstriction does not appear to be due to a relative paucity of pulmonary vascular smooth muscle. Likewise, the comparable rise in hematocrit in F-344 and WKY rats during chronic exposure to hypoxia (25) would argue against a generalized abnormality of perception of oxygen tension.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that there are significant differences in the vascular biology of these different rat strains. 34,35 Furthermore, there are differences in the vascular phenotype expression with aging between the strains. 36 One of the seminal features of the aging vasculature is an increase in arterial stiffness, which is additionally exacerbated by hypertension and diabetes.…”
Section: Discussionmentioning
confidence: 99%